5-Fluorouracil response in a large panel of colorectal cancer cell lines is associated with mismatch repair deficiency. - Bracht, K; Nicholls, A; Liu, Y; Bodmer, W (2010)
BACKGROUND: Colorectal cancer is (CRC) one of the commonest cancers and its therapy is still based on few drugs. Currently, no biological criteria are used to choose the most effective of the established drugs for treatment. METHODS: A panel of 77 CRC cell lines was tested for sensitivity to 5-fluorouracil (5FU) using the SRB assay. The responses were grouped into three categories and correlated with genetic changes in the cell lines. RESULTS: The strongest and most clearcut correlation was between 5-fluorouracil response and replication error status (mismatch repair deficiency). All the other significant correlations (loss of heterozygosity for DCC and mutations in TGFbIIR) are secondary to the association with replication error status. INTERPRETATION AND CONCLUSION: Our findings validate previous analyses based mainly on clinical data, and indicate that replication error status could be a useful guide to 5-fluorouracil-based CRC therapy. Essentially, all previously described correlations with 5FU response are secondary to the association with replication error status.